Age-dependent antibody profiles to plasmodium antigens are differentially associated with two artemisinin combination therapy outcomes in high transmission setting - Andagalu, Ben; Lu, Pinyi; Onyango, Irene; Bergmann-Leitner, Elke; Wasuna, Ruth; Odhiambo, Geoffrey; Chebon-Bore, Lorna J.; Ingasia, Luicer A.; Juma, Dennis W.; Opot, Benjamin; Cheruiyot, Agnes; Yeda, Redemptah; et al. (Frontiers in Medicine, 2022)
The impact of pre-existing immunity on the efficacy of artemisinin combination therapy is largely unknown. We performed in-depth profiling of serological responses in a therapeutic efficacy study (comparing ASMQ and AL) using a proteomic microarray. Responses to over 200 Plasmodium antigens were significantly associated with ASMQ treatment outcome but not AL. We used machine learning to develop predictive models of treatment outcome based on the immunoprofile data. The models predict treatment outcome for ASMQ with high (72-92%) accuracy, but could not predict treatment outcome for AL. This divergent treatment outcome suggests that humoral immunity may synergize with the longer mefloquine half-life to provide a prophylactic effect at 28 to 42 days post-treatment, which was further supported by simulated pharmacokinetic profiling. Our computational approach and modeling revealed the synergistic effect of pre-existing immunity in patients with drug combination that has an extended efficacy on providing long term treatment efficacy of ASMQ.